The impact of the acoustic environment on human emotion and experience: A case study of worship spaces. Issue 1 (March 2022) - Algargoosh, Alaa; Soleimani, Babak; O'Modhrain, Sile; Navvab, Mojtaba
People's interactions with the environment shape their experiences. Thus, understanding these interactions is critical to enhancing human well-being. Aural attributes play a significant role in shaping the perception of space in addition to visual attributes. It is well known that sounds evoke an emotional response, but less is known about how the acoustic characteristics of environments reinforce such an emotional impact. By adopting virtual reality as a platform for recreating 3D sounds and 360° visuals of built environments of worship spaces as case studies, this study aims to investigate the influence of the acoustic environment considering audiovisual congruency on enhancing the human experience through self-report and physiological response analysis. It also examines the role of cultural background in terms of familiarity with the acoustic environment. The convergent mixed-methods approach, merging both quantitative and qualitative analysis, provides a deep understanding of the role of the acoustic environment in enhancing the auditory experience. The results show that the acoustic environment and audiovisual congruency amplify the intensity of the emotional impact, and the amplification of the impact can vary depending on the acoustic environment of the building. They also reveal that familiarity with sound and acoustic characteristics can increase this impact.